Multilayers Polyethylene Film for Crop Protection in Harsh Climatic Conditions - A. Dehbi; B. Youssef; C. Chappey; A.-H. I. Mourad; P. Picuno; D. Statuto (Advances in Materials Science and Engineering)
In this work the performance and durability of a new generation of greenhouse covers, in which the cover is composed of five layers, are investigated. A sand wind ageing was performed under different exposure conditions. Surface morphology and chemical, physical, and thermal characteristics were investigated by using optical microscopy, FTIR, and tensile test techniques. In addition, the mechanical integrity of the five-layer film was assessed. The analysis indicated that the sand wind treatments have a significant influence only on the performance of the film. An attempt has been done to compare the properties of the five-layer film with the monolayer and trilayer films with or without air bubble under similar conditions. The results revealed that the five-layer film proved to be a promising greenhouse covering film.